A review of conventional and emerging technologies for hydrogels sterilization - S. A. Bento, Cristiana (2023)
Hydrogels are extensively used in the biomedical field, as drug delivery systems, wound dressings, contact lenses or as scaffolds for tissue engineering. Due to their polymeric nature and the presence of high amounts of water in their structure, hydrogels generally present high sensitivity to terminal sterilization. The establishment of an efficient sterilization protocol that does not compromise the functional properties of the hydrogels is one of the challenges faced by researchers when developing a hydrogel for a specific application. Yet, until very recently this aspect was largely ignored in the literature. The present paper reviews the state of literature concerning hydrogels sterilization, compiling the main findings. Conventional terminal sterilization methods (heat sterilization, radiation sterilization, and gas sterilization) as well as emerging sterilization techniques (ozone, supercritical carbon dioxide) are covered. Considerations about aseptic processing are also included. Additionally, and as a framework, hydrogels’ polymeric materials, types of networks, and main biomedical applications are summarily described.